Can Investors Detect Real Earnings Management during COVID-19? - Fernando Timotius; Astrid Rudyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to examine if investors are able to identify real earnings management during the COVID-19 crisis by assessing the impact of real earnings management on the firm value. This analysis uses 2020–2022 data from Indonesia Stock Exchange (BEI)-listed manufacturing companies. This study used purposive sampling to collect data from 153 companies, yielding 459 observations that met the criteria. Using multiple linear regression, this study finds that investors are able to identify real earnings management within the COVID-19 pandemic. Nevertheless, empirical evidence demonstrates that profitability exerts a detrimental impact on firm value. This study is among the initial investigations examining the impact of real earnings management on the firm value during the COVID-19 crisis